2019
DOI: 10.1002/npr2.12089
|View full text |Cite
|
Sign up to set email alerts
|

Blonanserin vs risperidone in Japanese patients with schizophrenia: A post hoc analysis of a phase 3, 8‐week, multicenter, double‐blind, randomized controlled study

Abstract: Objective To report the efficacy and safety of blonanserin in patients with schizophrenia compared with risperidone in a Japanese multicenter, randomized, double‐blind study based on post hoc sensitivity analysis in addition to the previous results reported by Miura and discuss the current approaches for schizophrenia treatment. Methods Of 302 patients randomized, 156 received blonanserin (8‐24 mg/d) and 145 received risperidone (2‐6 mg/d) for 8 weeks. Efficacy variables included the Positive and Negative Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…No deaths and only a few serious/severe AEs were observed. The types and incidence rates of AEs were similar between adolescents in the present study and adults in previous studies on blonanserin (Murasaki 2007 ; Miura 2008 ; Garcia et al 2009 ; Harvey et al 2019 , 2020 ). AEs caused by blonanserin in adolescent patients are considered as predictable as those in adult patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No deaths and only a few serious/severe AEs were observed. The types and incidence rates of AEs were similar between adolescents in the present study and adults in previous studies on blonanserin (Murasaki 2007 ; Miura 2008 ; Garcia et al 2009 ; Harvey et al 2019 , 2020 ). AEs caused by blonanserin in adolescent patients are considered as predictable as those in adult patients.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with adult schizophrenia, a randomized controlled study confirmed that blonanserin had greater efficacy than placebo in acute cases (Garcia et al 2009 ). Other randomized controlled studies confirmed the noninferior efficacy of blonanserin to haloperidol (Murasaki 2007 ; Harvey et al 2019 ), showing greater improvement in negative symptoms with fewer extrapyramidal adverse reactions than haloperidol as well as the noninferior efficacy of blonanserin to risperidone (Miura 2008 ; Harvey et al 2020 ), with the following differences in safety profile: compared with risperidone, blonanserin was associated with a lower risk of blood prolactin increase, weight gain, and orthostatic hypotension; however, blonanserin was associated with a higher incidence of akathisia and excitability than risperidone.…”
Section: Introductionmentioning
confidence: 88%
“…The types of adverse events were similar to those in the previous 8-week randomized, controlled studies of blonanserin in Japan [22][23][24][25]. Most of the events occurred within 8 weeks, and there was no increase of adverse events or new emergence of late-onset-type events due to long-term administration.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, BNS and N-deethyl body has low affinity for adrenaline α1, histamine H1, and muscarinic M1 receptors, which is related to the possible complications during the treatment of the drug. The clinical trials of BNS conducted in Japan, South Korea, and Europe consistently show that its efficacy is comparable with haloperidol and other second-generation antipsychotic drugs such as risperidone (4)(5)(6)(7). The incidence of side effects is lower, such as weight gain and prolactin elevation.…”
Section: Introductionmentioning
confidence: 95%